Colonialism, Feudalism, and the Collapse of Kejeruan Senembah during the Social Revolution in East Sumatra in 1946 - Nur’ Aini; Taslim Batu Bara (Medan Resource Center, 2026)
Colonialism and feudalism profoundly shaped the political structure of East Sumatra during the nineteenth and early twentieth centuries. Within this context, Kejeruan Senembah functioned as an influential local authority under the Deli Sultanate, deriving legitimacy from customary law (adat), genealogy, and Dutch colonial patronage. This study examines the factors underlying the collapse of Kejeruan Senembah during the East Sumatra Social Revolution of 1946. Employing historical methods comprising heuristics, source criticism, interpretation, and historiography, this research utilizes archival materials, colonial administrative records, historical manuscripts, and relevant secondary literature. The findings indicate that the collapse of Kejeruan Senembah was not solely caused by the violence of 4 March 1946, but constituted the culmination of prolonged social tensions arising from colonial domination, feudal inequality, and popular dissatisfaction with the traditional aristocracy. The revolution eliminated the political authority of Kejeruan Senembah, although its cultural identity and customary traditions continued to survive within the Karo-Malay community in Deli Serdang. This study contributes to the historiography of the East Sumatra Social Revolution by highlighting the neglected role of Kejeruan Senembah as a local political institution and by demonstrating how colonial and feudal structures eroded traditional authority.